Bridging the Gap Between Product Development and Entrepreneurship in Engineering Curriculum: A Framework-Based Approach Aligned with NEP 2020 - Shaikh Azharuddin Kutubuddin; Jahier Abbas Shaaikh; Lamkane Shashikant Hanmant (International Journal of Education Sciences, 2026)
Despite advancements in technical education, Indian engineering graduates frequently enter the workforce lacking critical competencies in product development (PD) and entrepreneurship. This imbalance has drawn scrutiny from industry and policymakers alike, with national directives such as the National Education Policy (NEP 2020) emphasizing a shift toward “experiential, holistic, integrated and inquiry-driven” learning models. Similarly, the All-India Council for Technical Education (AICTE) has embedded innovation labs, internship mandates and entrepreneurship courses into its revised model curriculum to cultivate job creators, not just job seekers. However, implementation remains fragmented across institutions. To address this, disconnect, this paper proposes a structured curricular framework that integrates PD and entrepreneurship (PD&E) across all four years of undergraduate engineering education. The proposed framework comprises five iterative stages: Discover, Define, Develop, Launch and Ecosystem. It offers a scalable pathway to embed innovation through coursework, studio-based activities and incubation linkages. A hypothetical case scenario involving an IoT-based “Smart Purifier” is utilized to illustrate the framework’s applicability. The model simultaneously addresses known skill gaps in communication, prototyping, intellectual property (IP) literacy and business modelling. Supported by policy mechanisms such as the National Innovation and Startup Policy (NISP) and the Institutional Innovation Council (IIC) network, this integrative approach seeks to align academic programs with the entrepreneurial and innovation imperatives of India's evolving knowledge economy.
Keywords: NEP 2020; curricular framework; entrepreneurship; higher education; product development; technical education